2011
DOI: 10.1089/neu.2010.1575
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Phosphodiesterase-4 Inhibitor Reduces Leukocyte Infiltration, Oxidative Processes, and Tissue Damage after Spinal Cord Injury

Abstract: We tested the hypothesis that a selective phosphodiesterase type 4 inhibitor (PDE4-I; IC486051) would attenuate early inflammatory and oxidative processes following spinal cord injury (SCI) when delivered during the first 3 days after injury. Rats receiving a moderately severe thoracic-clip-compression SCI were treated with the PDE4-I (0.5, 1.0, and 3.0 mg/kg IV) in bolus doses from 2-60 h post-injury. Doses at 0.5 mg/kg and 1.0 mg/kg significantly decreased myeloperoxidase (MPO) enzymatic activity (neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 53 publications
4
52
0
Order By: Relevance
“…59 Further, selective PDE4 inhibitors decrease hindpaw allodynia from compression SCI by reducing immune cell infiltration/activation and free radical formation. 5 PPF is a methyl-xanthine selective PDE4 inhibitor, 72 an isoform expressed in both microglia and astrocytes. 51 Although neurons express PDE4, PDE4 is the major isoform expressed in immune and inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…59 Further, selective PDE4 inhibitors decrease hindpaw allodynia from compression SCI by reducing immune cell infiltration/activation and free radical formation. 5 PPF is a methyl-xanthine selective PDE4 inhibitor, 72 an isoform expressed in both microglia and astrocytes. 51 Although neurons express PDE4, PDE4 is the major isoform expressed in immune and inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…This would imply that PDE4, which accounts for the majority of PDE activity in the CNS (Kleppisch, 2009), is the predominant PDE in immune cells (macrophages, eosinophils, neutrophils and microglia) (Semmler et al, 1993; Ghosh and Pearse, 2010) and has been identified in the injured spinal cord (Whitaker et al, 2008), could be regulated by pro-inflammatory cytokines such as TNF-α and IL-1β to decrease cyclic AMP. Rolipram, and other PDE4 inhibitors, in addition to preventing injury-induced decreases in cyclic AMP, also have potent anti-inflammatory actions (Bao et al, 2011; Atkins et al, 2007; Pearse et al, 2004b). Collectively this work implies that cyclic AMP dysregulation after CNS injury may be central to microglia activation and their ensuing auto-activation through pro-inflammatory cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Analysis of specific pain symptoms and signs related to IH in this case study also indirectly suggests a role for neuroinflammation in the development of local and remote cold allodynia. Acute cerebrospinal fluid levels of the inflammatory cytokine tumour necrosis factor-a has been correlated with NP shortly after SCI, 26 specifically with perception of 'sharp' pain, which is similar to the sensation described by our patient during the first month.…”
Section: Discussionmentioning
confidence: 61%